Três ensaios em economia da saúde - Rosa, Prisciane Raupp da (2022)
This thesis has as its theme the consequences of the 2019 Disease Caused by the Novel Coronavirus (Covid-19) pandemic on the economy, on chronic cardiovascular diseases and the implications of social, regional and epidemiological characteristics in deaths by Covid-19 and by cardiovascular diseases. In this way, it is possible to respond and assess the consequences of government actions in the economic context, in addition to identifying the relationships of social, geographic and epidemiological contexts that heterogeneously influenced deaths due to Covid-19 in Brazil and cardiovascular diseases, the main cause. of death and hospitalization in the country, especially in 2020 when there were still no vaccines to contain the pandemic. This analysis is done by responding to three proposals. The first is to analyze the direct and indirect impacts of emergency aid income transfers on the production of Brazilian states, verifying which states or regions are most benefited from these spillovers. The second is to identify and understand the role of regional economic and social factors associated with deaths from Covid19 in cities in Brazil in 2020. And the third is also to identify the regional economic and social factors associated with hospitalizations and deaths from cardiovascular diseases and verify the existence of impact of the pandemic and, particularly, on hospitalizations and deaths per 100 thousand inhabitants in Brazilian municipalities in 2020.